Correction to: Immunotherapy Utilizing the Combination of Natural Killer– and Antibody Dependent Cellular Cytotoxicity (ADCC)–Mediating Agents with Poly (ADP-ribose) polymerase (PARP) Inhibition. Issue 1 (2nd September 2019) - Fenerty, Kathleen E.; Padget, Michelle; Wolfson, Benjamin; Gameiro, Sofia R.; Su, Zhen; Lee, John H.; Rabizadeh, Shahrooz; Soon-Shiong, Patrick; Hodge, James W.
Abstract : Following publication of the original article [1], an error was noted in the GAPDH in the western blot depicted in Figure 4b.